2010
DOI: 10.1186/1471-2334-10-182
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin Use in Daily Clinical Practice for Treatment of Invasive Aspergillosis: Results of a Prospective Observational Registry

Abstract: BackgroundA prospective observational registry assessed real world experience with caspofungin monotherapy or combination therapy for the initial or salvage treatment of proven or probable invasive aspergillosis (IA).MethodsData were collected from April 2006 to September 2007 for patients treated with caspofungin for a single episode of IA. Clinical effectiveness was categorized as favorable (complete or partial) or unfavorable (stable disease or failure) at the end of caspofungin therapy (EOCT).ResultsConsec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 11 publications
(18 reference statements)
3
29
0
4
Order By: Relevance
“…A favorable response was observed in 45% (37/83) of patients, including 50% (32/64) of those with pulmonary aspergillosis and 23% (3/13) of those with a disseminated infection [68]. Another two prospective observation studies on salvage monotherapy with caspofungin reported a favorable response in 44% (20/45, mostly refractory to amphotericin B) and 56% (39/70) of patients [64,69]. Additionally, several retrospective studies have been published.…”
Section: Salvage Therapy For Invasive Aspergillosismentioning
confidence: 86%
See 1 more Smart Citation
“…A favorable response was observed in 45% (37/83) of patients, including 50% (32/64) of those with pulmonary aspergillosis and 23% (3/13) of those with a disseminated infection [68]. Another two prospective observation studies on salvage monotherapy with caspofungin reported a favorable response in 44% (20/45, mostly refractory to amphotericin B) and 56% (39/70) of patients [64,69]. Additionally, several retrospective studies have been published.…”
Section: Salvage Therapy For Invasive Aspergillosismentioning
confidence: 86%
“…In none of the two studies, serious drugrelated adverse events or discontinuations due to drugrelated adverse events were observed. In a recently published results from a prospective observational registry, caspofungin was used as first line therapy for IA in 20 patients (in 5 cases as a part of combination therapy), and 60% of patients in both groups (9/15 and 3/5) had a favorable (complete or partial) response [64]. Similarly, in 12 neutropenic patients with IA, 42% (5/12) responded to primary therapy with caspofungin [65].…”
Section: First Line Treatment Of Invasive Aspergillosismentioning
confidence: 94%
“…Finalmente, respecto a los hongos fi lamentosos, específi camente en el caso de Aspergillus, micafungina y caspofungina sólo tienen estudios en escenarios de rescate (falla de un antimicótico previo) [40][41][42] o en intolerancia 43 .…”
Section: Ensayos Clínicos De Efectividadunclassified
“…También es común la presencia de anormalidades de laboratorio, las cuales ocurren en diferentes frecuencias (entre 1 y 20%) como: hipopotasemia, hipoalbuminemia, elevación de aminotransferasas y aumento de fosfatasa alcalina son los más comunes 33,42 . Sin embargo, al com- www.sochinf.cl parar la frecuencia de ocurrencia de estos últimos entre caspofungina y anfotericina B, la incidencia fue mucho mayor con esta última (24,3 vs 54%); asimismo la nefrotoxicidad fue de 8,4% contra 24,8% respectivamente, del mismo modo que la hipokalemia 27 .…”
Section: Efectos Adversosunclassified
“…There is now an extensive, decade-long clinical experience using the echinocandin drugs anidulafungin, caspofungin, and micafungin to treat mucosal and invasive forms of candidiasis [1][2][3][4] as well as, on a limited basis, invasive aspergillosis [5]. Overall, the drugs demonstrate a high therapeutic index and excellent safety and tolerability profiles [6][7][8].…”
Section: Introductionmentioning
confidence: 98%